Gestão da capacidade inovativa e o poder de inovação sustentável - Rosa, Luciana Aparecida Barbieri da (2019)
Several studies have discussed the ability of business innovation from different perspectives, a key factor for the success and survival of organizations, which are competitive with competitors as a result of investments in innovation. The literature presents comprehensive content on respect for innovative capacity, which does not require catalysts and barriers to innovation. However, there is a presence of theoretical and empirical gaps that may explain its capacity for sustainable innovation. Given this, the objective of the study is to identify how the management of innovative capacity influences the power of sustainable innovation in Brazilian companies. To analyze the innovative capacity other than its catalysts, use the studies by Herrera (2016), Oslo Manual (2005) and Claudino et al (2017) and, which does not refer to barriers, the studies by Madrid Guijarro et al. (2009), D'Este, Iammarino, Savona, Von Tunzelmann (2012), Oslo Manual (2005) and Božić and Rajh (2016) and Claudino, et al (2017). To analyze the power of sustainable innovation, studies by Van Bonmell (2011) and Hallstedt, Thompson, Lindahl (2013) will be adopted. The first phase of the research was characterized as qualitative and was conducted from a multiple case study in four Brazilian companies. The results of this phase allow us to conclude that the innovative capacity considered high in the analyzed companies, evidenced in the association with the power of sustainable innovation. From the results of the qualitative stage, it was possible to confirm or pressure the study's leader that the innovative capacity and the power of sustainable innovation spread in the Brazilian business scenario. The second stage of the study was characterized as quantitative and comprised the conduct of a research with Brazilian companies. The results showed that innovative capacity is available with the power of sustainable innovation, as positive differences were shown between the dimensions of the dependent and independent variables. The applied bivariate and univariate analysis techniques (media difference and logistic regression) show the significant differences between the innovative capabilities and the power of innovation, being possible to confirm as outlined hypotheses.